PENGARUH SUPERVISI AKADEMIK KEPALA SEKOLAH DAN KOMPETENSI PEDAGOGIK GURU TERHADAP KINERJA GURU SEKOLAH MENENGAH PERTAMA (SMP) - Widyati, Endah; Budiman, Hendri; Elfisa, Yesi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of principals’ academic supervision and teachers’ pedagogical competence on junior high school teacher performance. A quantitative approach with an ex post facto design was employed because academic supervision and pedagogical competence had occurred naturally in the school context without any intervention from the researcher. The population comprised junior high school teachers, and the sample consisted of 72 teachers. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis used multiple linear regression preceded by assumption tests (normality, multicollinearity, and heteroscedasticity). The results showed that academic supervision had a positive and significant effect on teacher performance (Sig. = 0.001; B = 0.312), and pedagogical competence also had a positive and significant effect on teacher performance (Sig. = 0.000; B = 0.478). Simultaneously, academic supervision and pedagogical competence had a significant effect on teacher performance (Sig. = 0.000) with a coefficient of determination of R² = 0.532, indicating that both variables explained 53.2% of the variance in teacher performance. These findings highlight the importance of systematic, follow-up-oriented academic supervision and continuous development of teachers’ pedagogical competence to improve junior high school teacher performance. Keywords: Academic Supervision, Pedagogical Competence, Teacher Performance, Junior High School, Ex Post Facto.